2013
DOI: 10.1124/mol.112.083477
|View full text |Cite
|
Sign up to set email alerts
|

Protease-Activated Receptor (PAR) 1 and PAR4 Differentially Regulate Factor V Expression from Human Platelets

Abstract: With the recent interest of protease-activated receptors (PAR) 1 and PAR4 as possible targets for the treatment of thrombotic disorders, we compared the efficacy of protease-activated receptor (PAR)1 and PAR4 in the generation of procoagulant phenotypes on platelet membranes. PAR4-activating peptide (AP)-stimulated platelets promoted thrombin generation in plasma up to 5 minutes earlier than PAR1-AP-stimulated platelets. PAR4-AP-mediated factor V (FV) association with the platelet surface was 1.6-fold greater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
64
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 59 publications
(57 reference statements)
4
64
0
Order By: Relevance
“…However, results presented in the Bristol-Myers Squibb patent (Lawrence et al, 2013) around the efficacy of VU0652925 in reducing thrombus volume in a cynomolgus electrolytic carotid artery injury model of thrombosis with a PAR4 antagonist, and their movement into phase II clinical trials, speak to the relevance of these higher concentrations of thrombin and the efficacy of inhibiting their action on platelets. Precedent for the strong and superseding PAR4 response comes from work conducted by our group and others (Vretenbrant et al, 2007;Fälker et al, 2011;Duvernay et al, 2013). In our primary assay, we observed noncompetitive modes of inhibition for both SCH602539 and VU0652925.…”
Section: Discussionsupporting
confidence: 67%
“…However, results presented in the Bristol-Myers Squibb patent (Lawrence et al, 2013) around the efficacy of VU0652925 in reducing thrombus volume in a cynomolgus electrolytic carotid artery injury model of thrombosis with a PAR4 antagonist, and their movement into phase II clinical trials, speak to the relevance of these higher concentrations of thrombin and the efficacy of inhibiting their action on platelets. Precedent for the strong and superseding PAR4 response comes from work conducted by our group and others (Vretenbrant et al, 2007;Fälker et al, 2011;Duvernay et al, 2013). In our primary assay, we observed noncompetitive modes of inhibition for both SCH602539 and VU0652925.…”
Section: Discussionsupporting
confidence: 67%
“…Studies by Bevers et al in 1982 [5] clearly identified that collagen is more potent, but that the combination of collagen and thrombin greatly potentiated the capability of platelets to support thrombin formation [5]. The small percentage of phosphatidylserine (PS)-positive platelets reported in this paper are well in accordance with other studies [14,27,28], where only a small percentage of platelets turn PS positive even in response to high concentrations of thrombin, although it should be noticed that PS exposure determined by annexin V binding could vary considerably as a result of variations in experimental conditions [29]. The important contribution by collagen is also evident in this paper, as the combination of thrombin and collagenrelated peptide in Fig.…”
supporting
confidence: 90%
“…To be able to answer questions regarding the relative importance of PAR1 and PAR4 in the platelet procoagulant response, we need to study dose-responses to increasing concentrations of the specific receptor activating peptides. Such data are rare in previous publications, but studies by, for example, Duvernay et al and Vretenbrant et al [3,14] report a higher platelet activation with the most efficient PAR4-activating peptide, AYPGKF [15], as compared with the most potent PAR1-activating peptide, SFLLRN [16]. However, it should be kept in mind that the PAR4-activating peptides reach their maximum effects at concentrations 10-fold higher than the PAR1-activating peptides, which means that potential unspecific effects caused by the presence of the peptides themselves have to be considered as potential confounding factors.…”
mentioning
confidence: 93%
“…Under conditions similar to those used in this study, Factor V has been shown to be slowly released over approximately 10 minutes 21. The observation that AET platelets secrete significantly less Factor V than normal platelets, despite having normal levels of Factor V, is important for 2 reasons.…”
Section: Discussionmentioning
confidence: 60%